Acute exposure to long-chain fatty acids impairs {alpha}2-adrenergic receptor-mediated antilipolysis in human adipose tissue - Polák, Jan; Moro, Cedric; Bessiere, David; Hejnová, Jindra; Marques, Marie A; Bajzová, Magda; Lafontan, Max; Crampes, Francois; Berlan, Michel; Štich, Vladimír (Journal of lipid research, 2007)
The acute in vitro and in vivo effects of long-chain fatty acids (LCFAs) on the regulation of adrenergic lipolysis were investigated in human adipose tissue. The effect of a 2 h incubation, without or with LCFA (200 mumol/l), on basal and hormonally induced lipolysis was tested in vitro on isolated fat cells. The lipolytic response to epinephrine was enhanced by suppression of the antilipolytic alpha(2)-adrenergic effect. Then, healthy lean and obese male subjects performed a 45 min exercise bout at 50% of their heart rate reserve either after an overnight fast or 3 h after a high-fat meal (HFM: 95% fat, 5% carbohydrates). Subcutaneous adipose tissue lipolysis was measured by microdialysis in the presence or absence of an alpha-antagonist (phentolamine). In vivo, a HFM increased plasma levels of nonesterified fatty acids in lean and obese subjects. In both groups, the HFM did not alter hormonal responses to exercise. Under fasting conditions, the alpha(2)-adrenergic antilipolytic effect was more pronounced in obese than in lean subjects. The HFM totally suppressed the alpha(2)-adrenergic antilipolytic effect in lean and obese subjects during exercise. LCFAs per se, in vitro as well as in vivo, suppress alpha(2)-adrenergic-mediated antilipolysis in adipose tissue. LCFA-mediated suppression of antilipolytic pathways represents another mechanism whereby a high fat content in the diet might increase adipose tissue lipolysis.
Keywords: Insulin; Male; inzulin; alfa-2-adrenergní receptory; Obesity; mastné kyseliny; tuková tkáň; Microdialysis; obezita; Adult; dospělí; mužské pohlaví; Dietary Fats; Fatty Acids; potraviny; Food; Phentolamine; dietní tuky; lipolýza; mikrodialýza; lidé; Adipose Tissue; ženské pohlaví; Humans; fentolamin; Receptors, Adrenergic, alpha-2; Lipolysis; Financing, Organized; Female; financování organizované; lidé středního věku; Middle Aged